Dysfunctional customer behavior and service employees tactics - Antonio, Paloma; Espartel, Lélis Balestrin; Perin, Marcelo Gattermann (Revista de Administração da UFSM, 2019)
Dysfunctional customer behavior has grown substantially and has inspired academic research. In this theoretical study, the authors point out that the promotion of the myth of customer sovereignty through the culture of customer orientation is considered to be one of the variables that trigger these behaviors. The frontline employee manages the interactions in services and seeks to serve clients, but within the limitations of the offers. The discrepancy between the customers’ desires and what he obtains causes disillusionment and potentially dysfunctional behavior. Through their experience, employees accumulate tacit knowledge that grounds their assessment of situations and their development of tactics. On the other hand, organizations do not consider the dysfunctional customer behavior nor the tacit knowledge that exists in the service team in their strategies and actions, eventually not making use of this knowledge that could mitigate such behaviors. This is a theoretical article aimed at opening space for the debate of the dysfunctional customer behavior and service employees’ tactics through a theoretical composition that supports propositions and a conceptual model, as well as the suggestion of a future empirical test.